(untitled) (Applied Biological Research, 2019)
A study was performed in blood samples, collected from 15 healthy individuals during July to December 2017, to evaluate the integrity of DNA by preserving blood samples at three temperatures i.e. 4, -20 and -80ºC as against the fresh sample (control) for an incubation period of 30 days. DNA was extracted by standard protocol of phenol-chloroform and salting out method. The effect of temperature on DNA quality and quantity was analyzed spectrophotometerically, followed by amplification of Cytochrome p450 1A1 (CYP1A1) gene. In this prognosis, the study revealed that higher purity was attained at 4ºC, yield and concentration at -20ºC on extraction by phenol-chloroform. On contrary, in salting out method maximal yield and concentration was acquired at 4ºC and purity at -20ºC. Comparison of methods showed that phenol-chloroform method gave best result. DNA obtained from preserved blood samples is appropriate for amplification and further studies.